Predictors of uterine fibroid volume reduction under ulipristal acetate: a prospective MRI study. Issue 5 (November 2019) - Netter, Antoine; Pauly, Vanessa; Siles, Pascale; Pivano, Audrey; Vidal, Vincent; Agostini, Aubert
Abstract: Research question: Can patient and/or uterine fibroid characteristics predict the volume reduction of fibroids under ulipristal acetate (UPA) treatment? Design: This was a monocentric observational prospective cohort study of women with symptomatic fibroids who were willing to undergo surgery after a 3-month treatment of daily 5 mg doses of UPA. Patients underwent magnetic resonance imaging before and after treatment, and the volumes of the three largest fibroids were assessed. The reduction in volume was assessed qualitatively: fibroids decreasing in volume were considered to be 'responsive' to treatment, and fibroids that were stable or increased in volume were considered to be 'non-responsive'. Comparisons were made of patient (age and body mass index) and fibroid (initial volume, number and location) characteristics between fibroids that were responsive and non-responsive to UPA treatment. Results: Fifty-three women were included in the final analysis and 116 fibroids were measured. The initial number and initial volume of the fibroids were statistically associated with the response to UPA treatment (adjusted odds ratio [OR] 0.645, 95% confidence interval [CI] 0.461–0.903, P  = 0.0115 for number of fibroids, and adjusted OR 1.447, 95% CI 1.063–1.970, P  = 0.0195 for initial volume, with a log-linear relationship). Submucosal fibroids had a higher response rate to treatment (i.e. a decrease in volume) than intramural fibroids (21/25 [84.0%] versus 15/28 [53.6%]; P  = 0.0490; adjusted OR 4.478, 95% CI 1.007–19.918). Conclusions: The location, initial volume and number of fibroids may allow prediction of the outcome of a single 3-month treatment course of daily 5 mg doses of UPA in terms of reduction in volume before surgery.